CHANGES IN THE RETINA WITH TEN-WEEK OPIOID EXPOSURE WITH A SIMULTANEOUS FOUR- WEEK VASODILATOR CORRECTION - Soguiko, Yu.R.; Paltov, Ye.V.; Fik, V.B.; Masna, Z.Z.; Kowalska, M.Ye.; Krynytskyi, R.P.; Kryvko, Yu.Ya. (World of Medicine and Biology, 2021)
The purpose of our study was to establish pathomorphological manifestations of angio- and neuroretinopathy because of chronic exposure to therapeutic doses of opioid analgesic and possibilities of simultaneous correction of these changes with the help of pentoxifylline at the late terms of destructive changes in retinal layers. This was achieved by using histological methods of retinal imaging. In the future, the results of the study will allow forming a pathomorphological base with clinical recommendations for the unacceptable simultaneous application of opioids and pentoxifylline. The above mentioned will give an opportunity to access the most optimal time limits for which there is a characteristic set of pathomorphological manifestations of the initial phenomena of angioneuroretinopathy in the retinal layers, which is preferably exposed to corrective effect.
Keywords: retina; opioid; late terms; combined effect; rats